PMO-131 FGF inducible protein 14 is upregulated in neovessels during chronic inflammatory liver disease and promotes intrahepatic endothelial cell angiogenesis in vitro following stimulation via tweak. (28th May 2012) - Munir, M; Humphreys, E; Wilhelm, A; Stephenson, B; Caamano, J; Burkly, L; Adams, D; Afford, S
Abstract : Introduction: TWEAK and Fn14 members of the TNF superfamily of ligands and receptors collectively regulate a diverse range of immune, inflammatory and regenerative responses. Recent studies indicate a potential role of TWEAK and Fn14 in tissue repair following liver injury where they may promote angiogenesis and neovessel growth. TWEAK/Fn14 could therefore facilitate inflammatory cell recruitment and promote portal associated lymphoid tissue development during inflammation. Aims: (1). To investigate TWEAK/Fn14 expression in human liver tissue during chronic liver disease. (2) To study Fn14 expression in isolated intra-hepatic endothelial cells (IHEC). (3) To determine angiogenic responses of IHEC to TWEAK. Methods: Tissue sections from explanted human livers at the time of hepatobiliary surgery, including normal donor; normal tissue adjacent to malignant lesions; HCV; ALD; NASH; Chronic Allograft Rejection; PSC and PBC, were subjected to immunohistochemistry or dual immunofluorescence using antibodies to TWEAK, Fn14 and phenotypic markers CD31 and CD68. Isolated IHEC were cultured with combinations of TNFα, IFNg, FGF, and assessed for TWEAK/Fn14 expression using flow cytometry. In addition IHEC were incubated with recombinant TWEAK in presence ± TNFα and assessed using a matrigel angiogenesis assay for vessel formation and branching. Results: Fn14 expression was low in normal tissue in portal vessels and sinusoids, whereas in disease portal neovessels (CD31 +ve) were highly positive for Fn14. TWEAK expression was low in normal tissue but highly expressed in CD68+ve monocytic cells surrounding areas of neovascularisation and inflammatory cell aggregation. Fn14 expression significantly up-regulated on isolated IHEC when stimulated with the TNFα. Confocal imaging showed that the expression of Fn14 was predominantly cytoplasmic unless stimulated with TNF which enhanced cell surface expression. IHEC were consistently negative for TWEAK and TWEAK stimulation increased IHEC angiogenesis, where a change in cell morphology and enhanced branching of capillary like structures was observed. Pre-incubation with Fn14 antagonistic mAb completely abrogated vessel formation and branching. Conclusion: These new data show that Fn14 activation stimulates neovessel branching in IHEC and that TNF-α promotes mobilisation of cytoplasmic Fn14 to the cell surface suggesting an important regulatory role for TWEAK/Fn14 in neovascularisation and portal lymphoid aggregation during hepatic inflammation. Competing interests: None declared.